Use of a Trust Сonstruction for the Purpose to Control Affiliate and Inter-Group Connections Under the Laws of the Republic of Kazakhstan - S., Karagussov F.; J., Schramm H.; A, Tynybekov S.; R., Yermukhametova S.; A. Abikenov А. (Farabi Journal of Social Sciences, 2019)
Abstract. This Article includes a short analysis of a legal notion of trust and possibilities for practical use of various trust constructions known to English law or other legal system developed based on the Common law. General outcomes of such analysis are compared to notions of an affiliate person and controlling shareholder under the laws of Kazakhstan with the intention to find a solution for a major shareholder to retain his/her possession over a company’s shares but to avoid his/her qualification as a person exercising control over the company. The authors consider Kazakhstani judicial practice in the issue of determination of existence of a controlling power over a legal entity. It is argued that regulation of a trust management agreement by the Civil Code of Kazakhstan is not sufficient to provide a real independence of a trust manager from the founder and/or beneficiary. It is also noted that in such circumstances Kazakhstani court will unlikely find any ground for acknowledgement of a fact a founder of the trust management under Kazakhstan’s law does not have any controlling authorities over the company that shared belong to the founder. Futher research on reception of the trust concept has been recommended.